Comparation of the structural characteristics and biological activities of chondroitin sulfates extracted from notochord and backbone of Chinese sturgeon (Acipenser sinensis). (December 2022) - Meng, Dawei; Leng, Xiaoqian; Zhang, Yan; Luo, Jiang; Du, Hao; Takagi, Yasuaki; Dai, Zhiyuan; Wei, Qiwei
Abstract: To compare the structural properties and biological activities of chondroitin sulfate (CS) in two different tissues of Chinese sturgeon (Acipenser sinensis) and Russian sturgeon (Acipenser gueldenstaedti), we extracted their backbone cartilage CS (Cart-CS) and notochord CS (Noto-CS), and analyzed the CS structural properties using chromatographic and spectroscopic methods. The molecular weights of Chinese sturgeon Cart-CS and Noto-CS were 54.7 and 25.4 kDa, respectively, and the molecular weights of Russian sturgeon were 50.0 and 38.4 kDa, respectively. The disaccharide composition results showed that Cart-CS was mainly composed of CS-C, while Noto-CS was almost composed of pure CS-A. The antioxidant activity of sturgeon CS and its effect on collagen fibril formation were discussed. Sturgeon CS exhibited higher antioxidant activity than shark and bovine CSs. Sturgeon CS inhibited the self-assemble of type I collagen into fibrils. The inhibition effect of Cart-CS was higher than that of Noto-CS. The high value-added utilization of Cart-CS and Noto-CS will increase the value of sturgeon by-products. Furthermore, the disaccharide composition of CS in sturgeon depends on tissues of origin, but not on species. It means that the CS of Chinese sturgeon can be substituted by the CS of other commercial sturgeon. That will contribute to the protection of endangered species of Chinese sturgeon from illegal fishing and increase the value of commercial sturgeon by-products. Graphical abstract: Image 1 Highlights: Two kinds of CS were obtained from Acipenser sinensis and Acipenser gueldenstaedti. The average molecular weight of cartilage CS was higher than that of notochord CS. Cartilage CS was mainly composed by CS-C; Notochord CS was almost composed by CS-A. The inhibition of CS-C on collagen fibril-forming was higher than that of CS-A. The CS from Acipenser sinensis can be substituted by that from commercial sturgeon.